Parth Kohli
Reputation
4,557
Top tag
Next privilege 5,000 Rep.
Approve tag wiki edits
 Jun1 comment Why dividing by zero still works @J.M. Surprisingly, that is exactly what he also said. Jun1 comment Why dividing by zero still works Oh, that makes sense. Thanks! Jun1 asked Why dividing by zero still works May27 awarded Notable Question May26 comment Proving that either $2^n-1$ or $2^n+1$ is not prime Why are you not using \rm for variables today? May26 comment How to prove $\sum\limits_{n=1}^{\infty}\frac{\sin n}n=\frac{\pi-1}{2}$ That, my friend, is an epic observation. :-) May26 accepted What is $-i$ exactly? May25 comment Algebra Equation with equals on left hand side @amWhy Just saying, but some people who have started with algebra-precalculus may not understand what a relation is, let alone a symmetric relation. I think you should include a link which explains equivalence in classical logic as well as relations. Thanks :-) May24 comment How do you define definition symbol :=? := := :=, if you know what I mean. ;-) May24 comment What is $-i$ exactly? @AdrianPetrescu but 1 does have a sign, which is +, so we can use - to negate it. Here, I first focus on how -i cannot exist and then I say that even if it does, what differences are there between the two? May23 comment How to show $x^4 - 1296 = (x^3-6x^2+36x-216)(x+6)$ I agree. :-) ${}$ May23 comment How to show $x^4 - 1296 = (x^3-6x^2+36x-216)(x+6)$ (Mostly known as the synthetic division.) May23 comment How to show $x^4 - 1296 = (x^3-6x^2+36x-216)(x+6)$ Uh, actually I am saying that you wrote $a^4 - b^4 = a^3 + a^2 b + ab^2 + b^3$. It should be $a^4 - b^4 = (a - b)(a^3 + a^2 b + ab^2 + b^3)$ May23 comment How to show $x^4 - 1296 = (x^3-6x^2+36x-216)(x+6)$ $a^4 - b^4 = (a - b)(a^3 + a^2 b + ab^2 + b^3)$... May23 comment How to show $x^4 - 1296 = (x^3-6x^2+36x-216)(x+6)$ Note that the factorization is easily derivable by the Factor Theorem. May23 answered How to show $x^4 - 1296 = (x^3-6x^2+36x-216)(x+6)$ May22 comment Choice of numbers in calculating $\lim_{x\rightarrow 0}\frac{e^{2x}-1}{\sin 3x}$ I think what lab said suffices. May21 awarded Good Question May21 revised Determine the inverse function of $f(x)=3^{x-1}-2$ added 39 characters in body May21 answered Determine the inverse function of $f(x)=3^{x-1}-2$